2019
DOI: 10.4103/jmau.jmau_21_19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of suramin on renal proximal tubular cells damage induced by cisplatin in rats (histological and immunohistochemical study)

Abstract: Background:Renal toxicity is the most common complication of cispaltin therapy that has broad-spectrum antitumor activity against a variety of human solid tumor. Suramin, a Food and Drug Administration-approved old drug is a polysulfonated compound of napthylurea originally designed to treat trypanosomiasis.Aim:The current work aimed to investigate the possible protective effect of different doses of suramin against cisplatin-induced renal proximal tubular cells (RPTCs) damage.Material and Methods:Fifty adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Light microscopy studies of hepatic and renal tissues indicated marked damage in these tissues in DEX group. Such deviations in histoarchitecture signifying damage have been reported previously [29,[88][89][90]. The tissue sections from LycT+DEX group revealed less damage as compared to the DEX group.…”
Section: Discussionsupporting
confidence: 85%
“…Light microscopy studies of hepatic and renal tissues indicated marked damage in these tissues in DEX group. Such deviations in histoarchitecture signifying damage have been reported previously [29,[88][89][90]. The tissue sections from LycT+DEX group revealed less damage as compared to the DEX group.…”
Section: Discussionsupporting
confidence: 85%
“…In STZ‐induced diabetic rat models, isoflavones intake for 8 weeks increased the serum insulin level and reduced serum glucose, [ 21 ] genistein treatment showed protective and regenerative effects in pancreatic β‐cells. [ 22 ] Isoflavones supplementation failed to inhibit hyperglycaemia in KKAy mice, unlike in type 1 diabetes model, probably due to a pancreatic injury in this T2D model. Additionally, genistein reduced renal tubular cell death caused by ischemia/reperfusion injury [ 23 ] and cisplatin‐induced injury.…”
Section: Discussionmentioning
confidence: 86%
“…d ‐GalN induced liver injury and the development of renal failure in experimental animals as indicated by Gezginci‐Oktayoglu et al, 38 Hao et al 39 and El‐Kordy 11,40 . Also, it was shown that acute liver failure is accompanied by renal failure in 50% to 80% of patients 41,42 and declined renal blood flow that indicates renal vasoconstriction 43 .…”
Section: Discussionmentioning
confidence: 94%
“…D-GalN induced liver injury and the development of renal failure in experimental animals as indicated by Gezginci-Oktayoglu et al, 38 Hao et al 39 and El-Kordy. 11,40 Also, it was shown that acute liver failure is accompanied by renal failure in 50% to 80% of patients 41,42 and declined renal blood flow that indicates renal vasoconstriction. 43 Anand et al 15 Treatment with D-GalN resulted also in a significant increase of serum urea, creatinine, cystatin-C and neutrophil gelatinase-associated lipocalin levels which agrees with Ayhanci et al, 16 Sinha et al, 46 Dokumacioglu et al 47 Inflammation is a key factor in the pathogenesis of renal disease and it's progression.…”
Section: Discussionmentioning
confidence: 99%